Estimation of generation and gravimetric composition of solid wastes at Federal University of Campina Grande, Pombal, Paraíba, Brazil - Silva, Elisângela Maria da; Albuquerque, Walker Gomes de; Andrade Sobrinho, Luiz Gualberto; Medeiros, Amanda Nogueira (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The objective was to present the estimation of the per capita generation and gravimetric composition of the solid residues of the Center of Sciences and Agri-food technology of the Federal University of Campina Grande. These two characteristics are of fundamental importance in the solid waste management process. The methodological procedure was carried out by field survey to identify the number of sectors in the University Campus, as well as the quantification of the daily population that attends the institution. As a result, the daily per capita generation of the Science Center and Environmental Technology was 49.28 g. In relation to the gravimetric composition, it was verified that the organic matter had the highest percentage, representing a total of 66%, followed by 13% of plastics, 9% of paper / cardboard and 8% of composites. It is concluded that the largest part of the total solid waste generated is putrescible organic matter, which was already expected, since solid waste generated in the university campus presents characteristics of household waste.